2015
DOI: 10.1002/cjp2.11
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ATRX and DAXX expression identifies poor prognosis for smooth muscle tumours of uncertain malignant potential and early stage uterine leiomyosarcoma

Abstract: Uterine smooth muscle tumours of uncertain malignant potential (STUMP) are diagnostically and clinically challenging. The alternative lengthening of telomeres (ALT) telomere maintenance mechanism is associated with poor survival in soft tissue leiomyosarcoma. Time to first recurrence and survival were known for 18 STUMP and 43 leiomyosarcomata (LMS). These were screened for ALT telomere maintenance by the presence of ALT‐associated PML bodies (APBs) and for changes associated with the ALT phenotype, namely abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…All mutations were either nonsense or frameshift alterations most likely leading to a truncated protein product. Loss of ATRX expression has been reported in leiomyosarcomas of various sites [ 20 22 ] and a recent meeting abstract on ULMSs reported genomic alterations of this gene in 32% (8/25) of the studied tumors, supporting our findings [ 23 ]. We successfully analyzed ATRX protein levels in 44 ULMSs and showed that 52% of the tumors, including all reliably analyzed mutation-positive lesions, had clearly reduced expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All mutations were either nonsense or frameshift alterations most likely leading to a truncated protein product. Loss of ATRX expression has been reported in leiomyosarcomas of various sites [ 20 22 ] and a recent meeting abstract on ULMSs reported genomic alterations of this gene in 32% (8/25) of the studied tumors, supporting our findings [ 23 ]. We successfully analyzed ATRX protein levels in 44 ULMSs and showed that 52% of the tumors, including all reliably analyzed mutation-positive lesions, had clearly reduced expression.…”
Section: Discussionsupporting
confidence: 91%
“…In general, TP53 alterations are the most common genetic changes in human cancers and they are particularly associated with an aggressive phenotype. Recently, loss of ATRX expression was associated with poor clinical outcome in ULMS [ 21 , 22 ]. Larger sample series with information on both TP53 and ATRX are required to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a significant correlation between ALT activity and mutations or abnormal expression of ATRX chromatin remodeler and/or its binding partner H3.3-specific histone chaperone DAXX gene has been observed [9]. In particular, the loss of ATRX has been found to be highly associated with ALT-positivity in different subtypes of sarcomas with complex karyotypes [29], including dedifferentiated liposarcoma [24], angiosarcoma [30], and uterine smooth muscle tumors [31]. Moreover, the loss of ATRX or DAXX genes has been found to be associated with poor prognosis (i.e., death or recurrence) in smooth muscle tumors of uncertain malignant potential and early-stage uterine leiomyosarcoma [31].…”
Section: Ta Dfsmentioning
confidence: 99%
“…Most studies recently focused on molecular markers able to predict progression risk and prognosis of a LMS. Slatter et al correlated the presence of ALT and PML bodies (APBs) to a poor prognosis of LMS [52]. Next-generation sequencing confirmed the presence of ATRX mutations in LMS and their association with a poor survival [53].…”
Section: Molecular Featuresmentioning
confidence: 99%